2003
DOI: 10.1080/03009740310003758
|View full text |Cite
|
Sign up to set email alerts
|

Human synovium produces substances that inhibit DNA and stimulate proteoglycan and collagen synthesis by cultured human articular chondrocytes and synovial fibroblasts

Abstract: The effects of synovial conditioned medium (SCM) on DNA, proteoglycan (PG), and protein-collagen synthesis and respective gene expressions, in human articular chondrocytes (AC) and DNA synthesis in synovial fibroblasts (SFb), were studied in monolayer culture. All SCM exhibited concentration-dependent inhibition of [3H]thymidine incorporation in both AC and SFb. In contrast, SCM from three OA patients stimulated [35S]SO4 and [3H]glycine incorporations and the expression (RT-PCR) of aggrecan- and type II collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These reports indicate that the synovium in the transitional zone between the articular cartilage and the Synovial cells have been shown to have the ability to differentiate into chondrocytes in vitro [6,8,13]. Nishimura et al [10] described that the synovium harvested from the knees of New Zealand white rabbits was isolated and cultured in agarose suspension with TGF-b, and chondrogenesis was found with type II collagen positive.…”
Section: Discussionmentioning
confidence: 99%
“…These reports indicate that the synovium in the transitional zone between the articular cartilage and the Synovial cells have been shown to have the ability to differentiate into chondrocytes in vitro [6,8,13]. Nishimura et al [10] described that the synovium harvested from the knees of New Zealand white rabbits was isolated and cultured in agarose suspension with TGF-b, and chondrogenesis was found with type II collagen positive.…”
Section: Discussionmentioning
confidence: 99%
“…As we stated in the introduction, in a previous study, we observed that synovium located in the transitional zone between the articular cartilage and the synovial membrane invaded cartilage defects and exhibited chondrogenic potential in vivo [14]. Other studies have shown that synovial cells can differentiate into chondrocytes in vitro [1][2][3]10]. One study harvested synovium from the knees of New Zealand white rabbits, which was then isolated and cultured in agarose suspension with TGF-β, before being identified as type II collagen- Figure 1: Proliferation potential of cultured synovial cells in Group A (in which the synovium was harvested from the transitional zone between the articular cartilage and the synovial membrane at the femoral condyle) and Group B (in which the synovium was harvested from an area 5 mm medial to the transitional zone of the femoral condyle).…”
Section: Discussionmentioning
confidence: 70%
“…They described that the periosteal tissue adjacent to the synoviumcartilage junction has the potential to repair cartilage defects. Thus, recently the role of the synovium in the transitional zone between the articular cartilage and the synovial membrane in cartilage repair has been documented [1,[10][11][12][13]. Those reports indicate that the synovium in the transitional zone between the articular cartilage and the synovial membrane may have the potential to repair cartilage defects.…”
Section: Introduction and Our Previous Researchmentioning
confidence: 99%
“…Substances (glycoproteins, polysaccharides, and lipids) inhibit nucleic acid extraction or amplification in septic joints. 26,27 PCR also may lack sensitivity when a low inoculum of bacteria is present in the sample. This may be exacerbated when only a very small specimen volume (ie, Ͻ20 L) is available.…”
Section: Discussionmentioning
confidence: 99%